External debt and current account adjustments: The role of trade openness - Oyakhilome Wallace Ibhagui (Cogent Economics & Finance, 2018)
In this paper, we examine the various links among external debt, trade openness and current account in Sub-Saharan Africa, utilizing an approach that highlights current account from the perspective of saving and investment. We explore whether external debt aids the subsequent adjustment process of current account deficits in SSA. We also examine the role of openness in the adjustment process. Empirical analysis using large panel data samples of Sub-Saharan African countries between 1985 and 2013 shows that external debt mostly sets the tone for the subsequent adjustment of current account deficits in SSA. However, the current account deficits of countries with high openness expand significantly from increases in external debt. The results are robust to different time periods and econometric estimation techniques, the inclusion of other current account determinants as control variables and consideration of endogeneity.
Keywords: F30; F32; F40; 330; external debt; trade openness; current account balance; endogeneity